Assessment of the impact of treatment on quality of life of patients with haemophilia A at different ages: insights from two clinical trials on turoctocog alfa. (29th January 2014) - Santagostino, E.; Lentz, S. R.; Busk, A. K.; Regnault, A.; Iorio, A.
Summary Haemophilia and its treatment interfere with patients' life, so health‐related quality of life (HRQoL) should be assessed when evaluating treatments. This study investigated the HRQoL of patients with haemophilia A treated prophylactically with a new recombinant factor VIII. Two phase 3 trials investigated turoctocog alfa in patients with severe haemophilia A: one in children, one in adults and adolescents. HRQoL was a secondary endpoint assessed by the HAEMO‐QOL age‐specific, self‐administered questionnaires. Parent‐completed versions were also included for parents of children and adolescents. All HAEMO‐QOL questionnaires allow the calculation of domain‐specific and total scores ranging from 0 to 100, lower scores indicating better HRQoL. Mean change in all scores was described for 25 children aged 4–7 years, 21 children aged 8–12 years, 18 adolescents aged 13–18 years and 129 adults, overall, and according to the treatment regimen received prior to the study (on‐demand; prophylaxis; mixed). Mean changes in HAEMO‐QOL total score were 1.4 for children aged 4–7 years, −2.6 for children aged 8–12 years, −5.8 for adolescents and −1.6 for adults. In parent‐completed versions, mean changes in total score were −6.0 for children aged 4–7 years, −4.7 for children aged 8–12 years, and −10.0 for adolescents. Patients receiving on‐demand treatment before the trial showed greater improvement in HRQoL scores than patients already on prophylaxis. HRQoL of patients remained fairly stable over the course of the trials. However, improvements were observed for adolescents. Switching to prophylaxis was identified as a potential driver of improvement of HRQoL in patients with haemophilia A.